ИССЛЕДОВАНИЯ ВЛИЯНИЯ ФАКТОРОВ ВЯЗКОСТИ ВОДЫ И ЯВЛЕНИЯ СЕГРЕГАЦИИ НА ПОКАЗАТЕЛИ ОБОГАЩЕНИЯ ПОЛЕЗНЫХ ИСКОПАЕМЫХ - Васильев А.М. (My University, 2006)
Рассмотрен метод изучения явления сегрегации и полученные с его помощью количественные данные. Приведено влияние вязкости воды на показатели обогащения полезных ископаемых с разных точек зрения: теоретической и экспериментальной. После анализа соответствующей литературы сделан выбор формулы и проведен по ней расчет, который показал различия в средних скоростях потока движения воды по винтовой поверхности. В экспериментальной части проведены опыты на винтовом шлюзе ВШ-350.

In the given article the method of analysis of a phenomenon of a segregation and its quantitative datas, obtained with the help is reviewed, influence of viscosity of water on parameters of enrichment of minerals, from two different points of view is considered: theoretical and experimental. After gathering and the analysis of the corresponding literature the choice of the formula is made and calculation which has shown distinctions in average speeds of a stream of movement of water on a screw surface is made on it. In an experimental part, experiences on screw sluice VS-350 are lead.
Keywords: 658.52